Maritime domain awareness and India's maritime security strategy: Role, effectiveness and the way ahead. (2nd July 2020) - Gopal, Prakash
ABSTRACT: Maritime domain awareness (MDA) is a vital enabler of maritime security operations. For India it is a particularly important, yet challenging task, considering the complexity of the maritime neighbourhood in which it seeks to attain its strategic objectives. India's doctrinal articulations rightly identify MDA as a key operational enabler across the spectrum of maritime operations. Accordingly, the country and its maritime security agencies have invested significant effort in bolstering MDA capabilities, especially in the period after the Mumbai terror attacks of 2008. These efforts have resulted in substantial augmentation of platforms at the front-end of MDA operations, shore-based infrastructure, and in establishing international linkages for information-sharing. However, there are notable gaps in national MDA capabilities that may adversely impact the higher end of maritime operations. Mitigation of these shortcomings will require sustained focus in the immediate future, and a smart approach to capability accretion that ensures maximum returns on investment.